Engineered Agrobacterium improves transformation by mitigating plant immunity detection. Issue 6 (17th January 2023) - Yang, Fan; Li, Guangyong; Felix, Georg; Albert, Markus; Guo, Ming
Summary: Agrobacterium tumefaciens microbe‐associated molecular pattern elongation factor Tu (EF‐Tu) is perceived by orthologs of the Arabidopsis immune receptor EFR activating pattern‐triggered immunity (PTI) that causes reduced T‐DNA‐mediated transient expression. We altered EF‐Tu in A. tumefaciens to reduce PTI and improved transformation efficiency. A robust computational pipeline was established to detect EF‐Tu protein variation in a large set of plant bacterial species and identified EF‐Tu variants from bacterial pathogen Pseudomonas syringae pv. tomato DC3000 that allow the pathogen to escape EFR perception. Agrobacterium tumefaciens strains were engineered to substitute EF‐Tu with DC3000 variants and examined their transformation efficiency in plants. Elongation factor Tu variants with rarely occurred amino acid residues were identified within DC3000 EF‐Tu that mitigates recognition by EFR. Agrobacterium tumefaciens strains were engineered by expressing DC3000 EF‐Tu instead of native agrobacterial EF‐Tu and resulted in decreased plant immunity detection. These engineered A. tumefaciens strains displayed an increased efficiency in transient expression in both Arabidopsis thaliana and Camelina sativa . The results support the potential application of these strains as improved vehicles to introduce transgenic alleles into members of the Brassicaceae family.